Univalent functions with positive coefficients involving Touchard polynomials - Saurabh Porwal; Gangadharan MURUGUSUNDARAMOORTHY (Al-Qadisiyah Journal of Pure Science, 2020)
The purpose of the present paper is to establish connections between various subclasses of analyticunivalent functions by applying certain convolution operator involving Touchard polynomials. To be more precise, we investigatesuch connections with the classes of analytic univalent functionswith positive coefficients in the openunit disk $\mathbb{U}.$